Serum Bone Alkaline Phosphatase and Growth Hormone Levels May Help as a Diagnostic Criteria for Children with Amelogenesis Imperfecta - Didem Öner Özdaş; Sevgi Zorlu; Gamze Aren (Galenos Yayinevi, 2020)
Aim:The Amelogenesis Imperfecta (AI) term includes numerous inherited congenital enamel defects indicating clinical and genetic heterogeneity. The aim of the present study was to emphasize the importance of the potential prediction of AI via biochemical parameters.Materials and Methods:In total, 50 children were assessed in the study. The subjects included 13 syndromic AI, 22 isolated AI and 15 healthy children with a mean-age of 12.01±3.79 years old. The bone alkaline Phosphatase (BALP) and growth hormone (GH) blood levels of the children were evaluated. All data were statistically analysed by the SPSS 15.0 programme, one-way ANOVA and chi-square tests.Results:72.7% of syndromic AI and 47.6% of isolated AI group children have higher than normal BALP levels; 33% of syndromic AI and 28% of isolated AI group children have lower than normal blood GH levels. Subjects with AI have statistically significant abnormal blood BALP and GH levels and the presence of an Additional syndrome other than AI did not affect the results.Conclusion:Pediatricians may have a key role in early AI diagnosis via the evaluation of abnormal BALP and GH levels in blood tests and may help in providing comprehensive dental treatment in terms of prevention, prognosis and restoration of teeth in children with AI.